Comparison of Mineral Trioxide Aggregate and Biodentine for Open Apex Management in Children with Nonvital Immature Permanent Teeth: A Systematic Review - Ravindran, Vignesh; Jeevanandan, Ganesh; Marimuthu, Madhulaxmi; Panda, Suman; Syed, Ather Ahmed; Vishwanathaiah, Satish; Khanagar, Sanjeev; Maganur, Prabhadevi C. (European Journal of General Dentistry, 2022)
Tricalcium silicate cements have long been used in dentistry for management of open apex. Biodentine was introduced to overcome the disadvantages of mineral trioxide aggregate (MTA). The aim of this systematic review was to compare the success rates of biodentine and MTA as a material of choice for the management of open apex in children with nonvital immature permanent teeth. PubMed/Medline, Scopus, EMBASE, Cochrane, and Google Scholar were searched until November 30, 2021, with the search terms young permanent teeth, immature permanent teeth, open apex, MTA, and biodentine. Based on the inclusion criteria, the articles were selected following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and assessed for quality using a risk-of-bias assessment tool. The outcomes of the studies were qualitatively synthesized. A total of 379 studies were identified and after refinement only two studies met the eligibility criteria. Both the studies were performed in children with nonvital pulp status. One of the studies showed a clinical success of 91.66% for MTA and 100% for biodentine in revascularization cases while the other study showed 100% for both the materials in apexification cases. Radiographic success was 100% for both the materials at the end of the follow-up period in both the studies. Treatment modality can create heterogeneity that does not allow making a pooled conclusion for the two materials collectively, which is the case in this review where one study used revascularization, while the other used apexification. An overall high risk of bias was noticed for the selected studies. With high risk of bias and low quality of evidence, a strong definitive conclusion cannot be arrived at. Further studies with proper randomization and minimal risk of bias are required to provide a conclusive result. However, as per the included studies, biodentine can be a material of choice for revascularization while both MTA and biodentine can be used for apexification procedures.
Keywords: immature permanent teeth; mineral trioxide aggregate; biodentine; open apex